Deriving Value From Conversations About Your Brand - Fay, Brad; Larkin, Rick; Pauwels, Koen; Keller, Ed (MIT Sloan Management Review, 2019)
Companies often treat social media as the conversation that represents what consumers are saying about any given brand. But research shows that online and offline conversations are different beasts. Even though they both drive sales, they need to be measured and managed separately.